2016
DOI: 10.1111/jvim.13836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Inherited Neurologic Syndrome in Toyger Cats with Forebrain Commissural Malformations, Ventriculomegaly and Interhemispheric Cysts

Abstract: BackgroundIn children, frequent congenital malformations with concomitant agenesis of the corpus callosum are diagnosed by neuroimaging in association with other cerebral malformations, including interhemispheric cysts and ventriculomegaly. Similar studies providing full characterization of brain defects by in vivo magnetic resonance imaging (MRI), and correlations with the pertinent anatomic pathologic examinations are absent in veterinary medicine.Hypothesis/ObjectivesCongenital brain defects underlie the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer. Hydrocephalus and hydranencephaly have been found to occur concurrently with parvovirus infection (Tani et al 2001;Keating et al 2016). Taga et al (2000) reported acquired hydrocephalus and hydromyelia in a cat with FIP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer. Hydrocephalus and hydranencephaly have been found to occur concurrently with parvovirus infection (Tani et al 2001;Keating et al 2016). Taga et al (2000) reported acquired hydrocephalus and hydromyelia in a cat with FIP.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, dilation of the cerebral ventricular system is frequently secondary to viral infection (Tani et al 2001;Benigni and Lamb 2005;Hori et al 2015;Keating et al 2016). In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An extended family of mixed-breed cats derived from the Oriental breed has been characterized clinically and histopathologically with forebrain commissural malformation concurrent with ventriculomegaly and interhemispheric cysts [20]. These cats have small rounded ear pinnae and doming of the head (Figure 1).…”
Section: Introductionmentioning
confidence: 99%